The effect of hypnotically induced somatoform dissociation on the development of intrusions after an aversive film - Hagenaars, M; van Minnen, A; Holmes, E; Brewin, C; Hoogduin, K (2008)
Peritraumatic dissociation is thought to effect trauma information encoding, leading to PTSD symptoms like intrusive memories. Most studies have focused on peritraumatic psychological dissociation. The present experiment studied the impact of hypnotically induced somatoform dissociation (dissociative non-movement) versus deliberate non-movement during an aversive film on intrusion development. Seventy-nine participants were randomised into three conditions: dissociative non-movement (catalepsy), deliberate non-movement, and non-restricted control. Participants recorded their intrusions of the film in a diary for one week. In the dissociative non-movement condition, catalepsy effectively provoked somatoform dissociation. Spontaneous somatoform dissociation across conditions was positively related to implicit bias to film-related words and negatively related to explicit recall, but was not related to intrusion frequency. Dissociative non-movement and deliberate non-movement conditions combined had more intrusions than controls. However, the dissociative non-movement group did not have more intrusions than deliberate non-movement and control groups combined. The implications of these findings are discussed.